2015
DOI: 10.18805/ijar.5566
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis of three Chinese indigenous sheep breeds by microsatellite markers

Abstract: In this study, six microsatellite markers were adopted to detect the genetic diversity and analyze the genetic distance of three Chinese indigenous sheep breeds. The results showed that 161 alleles were detected in the three breeds of sheep populations, and the average effective number of alleles, the average polymorphism information content (PIC) of six microsatellite markers in fat-tailed sheep, small tailed han-sheep, Yuxi fat-tailed sheep were 5.8844, 6.3103, 4.8017 and 0.7463, 0.7790, 0.7140 respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
7
3
Order By: Relevance
“…Nei's genetic distances (Nei, 1972) between the five populations of sheep were calculated using 12 STR loci (Table 3), which varied from 0.469 to 0.217. The results of genetic distance of the present study were lower than the findings of Bai et al (2015), who reported that the genetic distance ranged from 0.21 to 0.62 for Chinese indigenous sheep breeds, which was higher than that of Egyptian sheep breeds (Rushdi et al, 2015). The values of genetic distances showed that the investigated sheep populations are characterized as having a high range of variability of the allele pool, presence or absence of certain alleles, and differences in frequency of occurrence alleles.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Nei's genetic distances (Nei, 1972) between the five populations of sheep were calculated using 12 STR loci (Table 3), which varied from 0.469 to 0.217. The results of genetic distance of the present study were lower than the findings of Bai et al (2015), who reported that the genetic distance ranged from 0.21 to 0.62 for Chinese indigenous sheep breeds, which was higher than that of Egyptian sheep breeds (Rushdi et al, 2015). The values of genetic distances showed that the investigated sheep populations are characterized as having a high range of variability of the allele pool, presence or absence of certain alleles, and differences in frequency of occurrence alleles.…”
Section: Discussioncontrasting
confidence: 94%
“…Today, the FAO and the ISAG-FAO Advisory Group on Animal Genetic Diversity recommend specific sets of STR (short tandem repeat, also known as microsatellite) loci for genetic analyses, such as for horse, cattle, and pig breeds. Of the different types of molecular markers, STRs are suitable for studying genetic diversity because of their abundancethe large amount of allelic variation at each locus is highly polymorphic, their distribution throughout the genome is random, and inheritance is codominant (Rekha et al, 2016;Barcaccia et al, 2013;Putman et al, 2014). In addition, STRs are able to generate information for the planning of crossings and further selection of genotypes in genetic breeding programs (Faleiro et al, 2007;Crispim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When Table 1 was analyzed in terms of PIC value, it was observed that there was a difference among quail lines. This value could be stated as higher than 0.477 (Kayang et al, 2002), but lower than 0.57 (Chang et al, 2007), 0.64 (Farrag et al, 2011), and 0.69 (Bai et al, 2013). Also, Tadano et al (2014) reported that of 49 polymorphic microsatellite markers, 55.1% were highly informative (PIC≥0.50), 28.6% were reasonably informative (0.50>PIC>0.25) and 16.3% were slightly informative (PIC ≤0.25) according to Botstein et al (1980) criteria.…”
Section: Discussionmentioning
confidence: 86%
“…This value could be informative for such studies according to Farrag et al (2011) who suggested that the average number of alleles per locus in the genetic studies distances must be >4 to reduce the standard error in the estimation of genetic distances. Average allele number found in studies that were carried on different quail genotypes by Chang et al (2007), Farrag et al (2011), Tadano et al (2014) and Bai et al (2013) as 2.33 to 5.67, 5.39, 5.20, and 5.3, respectively. As clearly seen here we found a higher allele number.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation